A Comprehensive Evaluation of Health Hazard Prevention Education Programs Targeting Online Activity Risks Among Students - Vineela, Kakarla; Grover, Jayant (Journal of Educational Research and Policies, 2025)
In this study the investigator aimed to find out the effectiveness of planned teaching on knowledge and practices regarding the prevention of health hazards related to online activities among students in the selected area. The child's physical and mental behavior is being affected by online education. This caused different health problems in school-age youngsters. The usage of mobile and other electronic media has risen for e-learning during the COVID 19 pandemic. The frequency of screenings and their effects on health have grown along with social media use and gaming. Electronic media has numerous negative physical and psychological effects, including poor nutrition, obesity, violence, aggressive behavior, tobacco and alcohol use, and attention problems. Research shows that screen violence makes children more aggressive, anxious, and fearful, especially for children under 8. Teenagers spend most of their time on social media, which can lead to risky behaviors like drinking, smoking, and sex. A survey by the Australian Psychological Association found that adolescents spend 3.3 hours a day on social media, impacting self-esteem and exposing them to strangers. Encouraging better use patterns may help minimize these harmful effects.